Implications of the Omnibus Law on Job Creation towards the Indonesian Forestry Sector - Sunarto Sunarto; Maya Shafira; Mashuril Anwar (Universitas Lampung, 2021)
The research aims to analyze the positive and negative implications of the omnibus law on job creation on the development of the forestry sector. In writing, this article is normative juridical. Based on this method, this research is conducted by examining and analyzing theories, doctrines, and laws and regulations that are relevant to the issues discussed. Based on research results, the main points of amendments to regulations in the forestry sector include affirmation of forest areas, forest areas, changes in forest area designation and function, utilization of production forests and protected forests, business permits, non-tax state revenues in the forestry sector, utilization of forest areas outside forestry activities, the authority of the central and regional governments in forest protection, prohibiting activities that cause forest destruction, and imposing sanctions and procedural law on criminal acts of forest destruction. These changes have implications for forest protection in Indonesia, including increasing forest area conversion, limiting community participation in forest management plans, and weakening sanctions (eliminating absolute responsibility). Therefore, in policy formulation, it is necessary to pay attention to forest protection to harmonize human and environmental interests. Based on the results of the research, it is therefore recommended that the government be firm and concrete in regulating forest protection efforts in future implementing regulations.